2008
DOI: 10.1002/ptr.2515
|View full text |Cite
|
Sign up to set email alerts
|

Bacopa monniera extract Induces apoptosis in murine sarcoma cells (S‐180)

Abstract: The Ayurvedic system of medicine recommends Bacopa monniera (BM) in the treatment of tumors. The present study aims to determine the mode of cell death induced by the ethanolic extract of BM in mouse S-180 cells. BM-treated S-180 cells were assessed for cell viability in a dose- and time-dependent manner using dye exclusion studies. Morphological changes in the BM-treated and untreated cells were studied by transmission electron microscopy (TEM). Glutathione (GSH) levels were quantified and the percentage of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…A number of studies have suggested that certain bioactive chemicals present in plants may protect against inflammation (Plummer et al ., 1999; Murakami and Ohigashi, 2007). Bacopa monniera (L.) Wettst (family: Scrophulariaceae family) is a renowned Ayurvedic plant reported to possess memory‐enhancing (Mukherjee and Dey, 1996), cognitive (Vohora et al ., 2000), antioxidant (Chowdhuri et al ., 2002), anti‐fertility (Singh and Singh, 2009), hepatoprotective (Vijayan and Helen, 2007), anti‐cancer (Rohini and Devi, 2008), anti‐ulcer (Sairam et al ., 2001) and anti‐inflammatory (Viji and Helen, 2008) properties. The plant is enriched with many phytochemicals of which betulinic acid (BA), a triterpenoid belonging to lupane series, was recently explored to its topoisomerase inhibitory potential (Chowdhury et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that certain bioactive chemicals present in plants may protect against inflammation (Plummer et al ., 1999; Murakami and Ohigashi, 2007). Bacopa monniera (L.) Wettst (family: Scrophulariaceae family) is a renowned Ayurvedic plant reported to possess memory‐enhancing (Mukherjee and Dey, 1996), cognitive (Vohora et al ., 2000), antioxidant (Chowdhuri et al ., 2002), anti‐fertility (Singh and Singh, 2009), hepatoprotective (Vijayan and Helen, 2007), anti‐cancer (Rohini and Devi, 2008), anti‐ulcer (Sairam et al ., 2001) and anti‐inflammatory (Viji and Helen, 2008) properties. The plant is enriched with many phytochemicals of which betulinic acid (BA), a triterpenoid belonging to lupane series, was recently explored to its topoisomerase inhibitory potential (Chowdhury et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Bacopa monniera commonly as Bacopa monnieri, Herpestis monniera, water hyssop, thyme leafed gratiola or Brahmi is a member of the Scrophulariaceae family. It is widely distributed in marshy areas, and has been reported to possess memory enhancing [8], cognitive [9], antioxidant [10], antifertility [11], hepatoprotective [12], anti-cancer [13], anti-ulcer [14] and anti-inflammatory [15] properties. Bacopa monniera is traditionally and anecdotally used for the management of rheumatic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…One such plant that has been used to cure inflammation is Bacopa monniera (Brahmi), a member of the Scrophulariaceae family. Renowned in the Ayurvedic system of medicine, this herb is reported to possess cognitive (Zhou et al 2009), anti-fertility (Singh and Singh 2009), hepatoprotective (Vijayan and Helen 2007), anti-cancer (Rohini and Devi 2008), antioxidant (Chowdhury et al 2002), anti-ulcer (Sairam et al 2001) and anti-inflammatory (Viji and Helen 2008) properties. Bacopa monniera extract counters oxidative stress by scavenging reactive oxygen species, inhibiting lipoxygenase activity and reducing divalent metals (Dhanasekaran et al 2007).…”
Section: Introductionmentioning
confidence: 97%